Career Development Strategies for Vocational Students in the Digital Era - Novita Eka Muliawati; Tri Wahyuni; Henny Pratiwi; Lilik Nur Aini; Tuwoso Tuwoso (International Journal of Educational Evaluation and Policy Analysis, 2025)
The digital era has brought significant changes in various aspects of life, including in the fields of education and career development. Vocational High School students are faced with challenges to prepare themselves for an increasingly competitive and technology-based world of work. This study aims to identify effective career development strategies for vocational students in the digital era. Through literature analysis and case studies, this research found that the utilization of information technology, soft skills development, and collaboration with industry are key to improving students' work readiness. The results of this study are expected to provide insights for educators, students, and stakeholders in formulating career development programs that are relevant and adaptive to the needs of the labor market.